Patenting Deal in Indonesia, Article 20 of The Patent Law in The Political Perspective of International Trade Law - Mahoro Jean Claude Geofrey; Kholis Roisah (LAW REFORM, 2020)
The research at hand analyses the legal foundation of Article 20 of the Indonesian Patent Law No 13 of 2016. It assesses its conformity with the WTO Agreements known as the Uruguay Round, specifically the TRIPS Agreement. Those agreements have a character of ‘hard law,’ which compels all the WTO Members to be bound by them. Patent law and other Intellectual Property Rights (IPRs), any WTO Member must implement the minimum standards stipulated under the TRIPS Agreement in its national legal system without discrimination. In this light, Indonesia, as a WTO member since 1994, must comply with all WTO Agreements,. Therefor, it made various law reforms in the protection of IPRs. However, the Patent Law raised a debate that it contradicts the principles of international trade law as it embodies a discriminatory provision that only safeguards the people of Indonesia. As a result, the present found that, based on limited exceptions stipulated in the TRIPS and the Paris Convention, Indonesia did not violate the TRIPS as it applied a given leeway for implementing the TRIPS Agreement in a domestic context. Thus, it had reasonable grounds to secure its nationals’ mutual interest without violating general provisions and principles stipulated in the WTO Agreements.